Investigation on the modeling and dynamic characteristics of a fast-response and large-flow water hydraulic proportional cartridge valve. (November 2020) - Han, Mingxing; Liu, Yinshui; Zheng, Kan; Ding, Youchun; Wu, Defa
In large-power and high-pressure hydraulic systems, the maximum instantaneous flow rate is often several thousand liters per minute. Normal proportional valves are often difficult to meet their requirements for large flow rate and fast response at the same time. And the leakage of hydraulic oil will seriously pollute the environment. Therefore, a novel water hydraulic proportional valve with fast response and high flow capacity is presented for the large transient power hydraulic system in this paper. The valve utilizes a two-stage structure with two 2/2-way water hydraulic proportional valves as the pilot stage and a cartridge poppet valve as the main stage to achieve fast-response and large-flow capacity simultaneously. A detailed and precise nonlinear mathematical model of the valve considering both structural parameters and flow force is developed. A comprehensive performance optimization has been carried out, which can be mainly divided into computational fluid dynamics simulation optimization based on reducing flow force and multi-objective optimization based on genetic algorithm. The effects of double U-grooves' parameters on the flow force (flow-induced loads) have been studied in detail by numerical simulation. Through the grooves geometry optimization, the maximum flow force can be reduced by 10%. Then, the influences of structure parameters on the performance of step response have been studied, and the optimal parameters of the valve have been obtained by multi-objective optimization based on genetic algorithm. The maximum overshoot has been reduced from 15% to 6% (about 60%) and the adjusting time has been reduced from 58 ms to 48 ms. The dynamic characteristics of the valve have been improved effectively. Finally, a test apparatus which has the ability to provide transient large flow is built. The accuracy of simulation model and optimization design method is verified by test results.